STRENGTHENING THE NATIONAL AIR DEFENSE SYSTEM TO COUNTER DRONE THREATS AND AIR ATTACKS IN JAKARTA AS INDONESIA'S CENTER OF GRAVITY - Kutoyo; Margaretha Hanita; Eko Daryanto (RADJA PUBLIKA, 2025)
Jakarta, as the capital city and the center of gravity of Indonesia, is highly vulnerable to modern aerial threats. Its dense population, the presence of government institutions, vital infrastructures, and its role as the nation's political, economic, and diplomatic hub make Jakarta a strategic target for drone attacks and aerial strikes. These threats are asymmetric in nature—fast, precise, difficult to detect, and cost-effective—thus requiring the strengthening of an adaptive and integrated air defense system. This study employs a qualitative descriptive-analytical approach through literature reviews, policy document analysis, and comparative case studies of international practices. The findings reveal that integrating advanced radar technology, early warning systems, Counter-Unmanned Aerial Systems (C-UAS), and the readiness of the Indonesian Air Force are crucial in establishing a layered air defense system in Jakarta. These efforts align with Indonesia's total defense doctrine, emphasizing cross-sector synergy, military-civil collaboration, and defense diplomacy to safeguard national stability.